2017
DOI: 10.1002/aenm.201701586
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Efficiency Loss of Perovskite Solar Cells by a Modified Detailed Balance Model

Abstract: mechanism and quantify the efficiency loss for perovskite solar cells.The analysis and quantification of efficiency loss of solar cells can be done by the drift-diffusion model, [24,25] circuit model, [26,27] and detailed balance model. [28,29] Due to a high nonlinearity of coupled equations and a complex device configuration, drift-diffusion model is difficult to retrieve simulation parameters from the measured current density-voltage (J-V) curves. The parameters include recombination rate, mobility, energy l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
73
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(73 citation statements)
references
References 40 publications
0
73
0
Order By: Relevance
“…Taking PSCs for example, the first critical question comes to, how to reduce the optical loss and thus maximize the light harvesting efficiency within the PSCs? It has been reported that the optical loss in PSCs climbs up to 40% for the device based on the MAPbI 3 thin film with the thicknesses less than 240 nm, which means a large portion of incident light could not be efficiently absorbed and thus lowering the photocurrent density ( J sc ) . To approach the Shockley–Queisser efficiency limit of PSCs (≈31%), a more effective light management should be conducted.…”
Section: Diverse Perovskite Morphologies For Optoelectronic Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking PSCs for example, the first critical question comes to, how to reduce the optical loss and thus maximize the light harvesting efficiency within the PSCs? It has been reported that the optical loss in PSCs climbs up to 40% for the device based on the MAPbI 3 thin film with the thicknesses less than 240 nm, which means a large portion of incident light could not be efficiently absorbed and thus lowering the photocurrent density ( J sc ) . To approach the Shockley–Queisser efficiency limit of PSCs (≈31%), a more effective light management should be conducted.…”
Section: Diverse Perovskite Morphologies For Optoelectronic Applicationsmentioning
confidence: 99%
“…In recent years, various low‐dimensional halide perovskites including 0D quantum dots (QDs), nanocrystals (NCs), 1D nanowires (NWs),8b,13 2D nanoplatelets (NPLs), and nanosheets (NSs) have been demonstrated as promising alternatives for obtaining fruitful progress in solar cells, LEDs, photodetectors, and lasers,8b owing to their unique quantum confinement effect, large surface‐to‐volume ratio, and anisotropic geometry . In addition, it is worth pointing out the emergence of textured perovskite, which show significantly distinct morphological features, namely, the porous matrix, rough surface, and preferential grains orientation.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, PSCs with inverted planar structures have drawn great attention due to their low‐temperature solution‐process fabrication, which is compatible with roll‐to‐roll and flexible process and can be simply integrated into tandem solar cells . However, the device performance of inverted PSCs still lags behind that of regular structured PSCs, probably due to distinct open‐circuit voltage ( V OC ) loss induced by surface recombination . An effective surface modification is a still great challenge for pursuing higher‐performance inverted planar heterojunction PSCs.…”
Section: Introductionmentioning
confidence: 99%
“…The electrode contact and electron transport material are two of the most important considerations when developing perovskite (PVK) films, which are mainly attributed to complicated surface conditions with different types of defects formed on the exposed film surface during varied film forming and subsequent annealing processes . Accordingly, a variety of interfacial materials and various passivation techniques have been developed, and fullerenes, such as buckminsterfullerene (C60) or their derivatives, are the most popular electron transport materials for inverted structure PSCs .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Wei et al reported that the maximum limit for conversion efficiency is 31%. They have also certified that the efficiency limit of perovskite can be improved with light trapping through h texturing [21].…”
Section: Theoretical Limitations In the Performance Of Perovskite Solmentioning
confidence: 99%